Survey side effects of transferring neonates to specialized center in Esfahan on the neonatal mortality rate - Z. Parsa yekta; L. Barimnejad (Tehran University of Medical Sciences, 2001)
This was an analytical-descriptive study on determination of relationship between physiological variables of the neonates when admitted to the neonatal intensive care unit and mortality rate amony transferred neonates to a specialized center of Esfahan university of medical sciences."nIn this research, seventy neonates who were transferred to this center were randomly according to Poasan model selected."nOn the time of admitting neonates to this center, their VS, BS and ABG were immediately checked and the results recordered. The neonates were followed until they were discharged or expired. For data analysis, the descriptive statistical methods and Spearman correlational coefficient were used."nThe results indicated that 31.4% of the transferred neonates expired. The relationship between mortality rate and birth weight was meaningful. Furthermore, there was a significant relationship in physiological variables of the neonates when admitted to the neonatal intensive care unit(P<0.01)."nThese results can be applied in nursing services management, nursing education and national programming in order to establish special teams for neonatal transferring.